European and American extreme right groups and the Internet - Caiani, Manuela; Parenti, Linda (Routledge, 2016)
How do right-wing extremist organizations throughout the world use the Internet as a tool for communication and recruitment? What is its role in identity-building within radical right-wing groups and how do they use the Internet to set their agenda, build contacts, spread their ideology and encourage mobilization? This important contribution to the field of Internet politics adopts a social movement perspective to address and examine these important questions. Conducting a comparative content analysis of more than 500 extreme right organizational web sites from France, Germany, Italy, Spain, the United Kingdom and the United States, it offers an overview of the Internet communication activities of these groups and systematically maps and analyses the links and structure of the virtual communities of the extreme right. Based on reports from the daily press the book presents a protest event analysis of right wing groups' mobilisation and action strategies, relating them to their online practices. In doing so it exposes the new challenges and opportunities the Internet presents to the groups themselves and the societies in which they exist.